2023
DOI: 10.2196/41973
|View full text |Cite
|
Sign up to set email alerts
|

The Associations of Weekend Warrior Activity Patterns With the Visceral Adiposity Index in US Adults: Repeated Cross-sectional Study

Abstract: Background According to previous reports, obesity especially visceral fat has become an important public health problem, causing an estimation of 20.5 disability-adjusted life years per 1000 inhabitants. Those who exercised for 1 or 2 days per week and reached the recommended 150 minutes of moderate physical activity (PA) per week have been defined as “weekend warriors” (WWs). Although the benefits of PA in suppressing obesity have been widely studied, the association of WWs with the Visceral Adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 35 publications
(39 reference statements)
1
16
0
Order By: Relevance
“…A systematic review and meta-analysis with 15 cohort studies showed similar protective effects and that the maximum benefit was obtained from those meeting the recommended guidelines by either moderate or vigorous-intensity activities 26. Recently, a cross-sectional study from National Health and Nutrition Examination Survey (NHANES) also revealed the protective effect of physical activity against depression 34. Additionally, several epidemiological studies among the Chinese also revealed a similar beneficial role of physical activity in decreasing depression risk,35–38 while sedentary behaviour was positively associated with depression in a dose-response manner 39.…”
Section: Discussionmentioning
confidence: 93%
“…A systematic review and meta-analysis with 15 cohort studies showed similar protective effects and that the maximum benefit was obtained from those meeting the recommended guidelines by either moderate or vigorous-intensity activities 26. Recently, a cross-sectional study from National Health and Nutrition Examination Survey (NHANES) also revealed the protective effect of physical activity against depression 34. Additionally, several epidemiological studies among the Chinese also revealed a similar beneficial role of physical activity in decreasing depression risk,35–38 while sedentary behaviour was positively associated with depression in a dose-response manner 39.…”
Section: Discussionmentioning
confidence: 93%
“…Scarce literature has discussed whether the effects of reducing fat in WW differ from those in RA. Only one study, to our knowledge, has assessed the association between PA patterns and VAI and found a similarly lower VAI between WW and RA [10]. However, the VAI is a surrogate marker for VAT dysfunction and is calculated based on blood lipids and anthropometric parameters [27], which cannot directly reflect other adipose tissues, such as abdomen and whole‐body fat assessed by DXA.…”
Section: Discussionmentioning
confidence: 99%
“…First, participants with anxiety, depression symptoms and poor sleep quality may experience great stress during their life, [27][28][29][30] and then result in the activation of sympathetic excitation, which was associated with the occurrence of CKD. Second, participants with these problems may cause endocrine disruption and changes in hormone levels, [31][32][33] which was associated with CKD.…”
Section: Discussionmentioning
confidence: 99%